REVIEW ON HERBAL LOZENGES PREPARED FOR COLD AND FLU. - Mudgal Kajal; S, Koko Sweta.; N, Darwhekar G. (Journal of Biomedical and Pharmaceutical Research, 2021)
Traditional medicine and herbal formulation have been used by mankind for the care and treatment of various diseases and disorder. Throat infections are most common diseases in today’s world. However it is not taken too seriously by people long term throat infection can lead to severe throat problems pharyngitis and also cancer. The polyherbal lozenges are solid preparation that contains one or more medicaments usually during a flavored, sweetened base that are intended to dissolve or disintegrate slowly within the mouth. The benefits of they medicated lozenges is that they increase a retention time of the dosage form in mouth which increases bioavailability, reduces gastric irritation and bypasses first pass metabolism. Keywords: polyherbal lozenges, pharyngitis